2022
DOI: 10.1177/11769351221096655
|View full text |Cite
|
Sign up to set email alerts
|

A BIRC5High COD1Low Cancer Tissue Phenotype Indicates Poorer Prognosis of Metastatic Breast Cancer Patients

Abstract: Extensive data research is helpful to find sensitive biomarkers for prognostic prediction of metastatic breast cancer. Through analyzing multiple GEO datasets, literature retrieval, and verified in GEPIA datasets, we identify BIRC5 (Baculoviral IAP repeat containing 5) and CDO1 (Cysteine dioxygenase type 1) as DEGs (differentially expressed genes) between breast tumor and normal tissue and DEGs between metastatic breast cancer and breast cancer in situ. Then, we performed a series of in silico studies on BIRC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The advent of bioinformatics has dramatically increased the speed of screening for tumor markers. The studies have demonstrated that bioinformatics screening for tumor markers is a reliable method [6][7][8]. Therefore, bioinformatics is expected to screen new gastric cancer markers more quickly with excellent specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of bioinformatics has dramatically increased the speed of screening for tumor markers. The studies have demonstrated that bioinformatics screening for tumor markers is a reliable method [6][7][8]. Therefore, bioinformatics is expected to screen new gastric cancer markers more quickly with excellent specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%